การหาตำแหน่งจุดดัชนีโดยอัตโนมัติด้วยเทคนิคการจับคู่ภาพ - ธีระ ลิลิตวรางกูร (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The thesis is a study of automatically positioning of 8 fiducial marks on the digital arial photograph using image matching technique. Four methods of finding center of fiducial marks were summarized and evaluated, namely, manual locating, center of gravity, correlation coefficient, and least square methods. All methods were then implemented and tested on 8-bit gray-scale images with the pixel size of 15, 30 and 60 micron. The positions given from those method are integer and decimal. The research is also to develop a computer program using C language to calculate the coordinate by center of gravity, correlation coefficient, and least square methods. Then the performances of each were compared considering of precision, time consuming, and reliability. The results revealed that when using implemented program to calculate the fiducial marks on the digital photo, By using center of gravity method as reference the center of fiducial marks from least square methods are within 0.2 pixel. The method of correlation coefficient with sub-pixel accuracy type are within 0.4 pixel. For time consumption, the center of gravity method took 1.5 second per 8 fiducial marks which is the fastest, while the correlation coefficient method and least square methods need 1.7 and 4.2 seconds, respectively. In term of reliability, the coordinate calculated from center of gravity method was mostly closed to those from manual locating method and is ausummed to most reliable.